Effects of dried distillers grains with solubles and increasing dietary wheat middlings on growth performance, carcass characteristics, and fat quality in growing-finishing pigs - Barnes, J.A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 288 pigs (PIC TR4 × 1050, initially 100 lb) were used in an 84-d growth trial to evaluate the effects of dietary wheat middlings and dried distillers grain with solubles (DDGS) on growing-finishing pig growth performance, carcass characteristics, and carcass fat quality. Pens of pigs were balanced by initial weight and gender and were randomly allotted to 1 of 4 dietary treatments with 8 pigs per pen (4 barrows and 4 gilts) and 9 replications per treatment. Dietary treatments included a corn-soybean meal-based diet, a diet with 30% DDGS, or the diet with 30% DDGS with 10% or 20% wheat middlings. Treatment diets were formulated to constant standardized ileal digestible lysine:ME ratios within each phase. All treatments were fed in 4 phases. Overall (d 0 to 84), pigs fed increasing wheat middlings had decreased (linear; P ≤ 0.02) ADG and poorer (linear; P ≤ 0.01) F/G. There were no differences (P = 0.12) among treatments for ADFI. For carcass characteristics, increasing wheat middlings decreased (linear; P < 0.01) percentage yield and HCW and tended to decrease (linear; P < 0.06) loin depth. Pigs fed wheat middlings also had decreased (quadratic; P < 0.02) back fat and increased (quadratic; P < 0.01) percentage lean. Increasing DDGS from 0 to 30% decreased (P < 0.03) carcass yield and backfat depth (P < 0.01), while increasing percentage lean (P < 0.03) and jowl iodine value (P < 0.001). Increasing wheat middlings in the diet decreased (linear; P < 0.006) feed cost per pig and feed cost per lb gain but also decreased (linear; P < 0.008) total revenue. Similarly, feeding DDGS decreased (P < 0.001) feed cost per pig and feed cost per lb gain; however, because total revenue was not decreased as greatly by DDGS, feeding 30% DDGS increased (P < 0.001) income over feed costs (IOFC). In conclusion, alternative ingredients, such as DDGS and wheat middlings, can reduce feed cost; however, the full impact on growth performance and carcass value must be known to truly understand whether they influence net profitability.
Keywords: Swine; Dried distillers grains with solubles; Iodine value; Wheat middlings